Boosting the activity of hydrogen release from liquid organic hydrogen carrier systems by sulfur-additives to Pt on alumina catalysts. Issue 13 (18th June 2019) - Auer, Franziska; Blaumeiser, Dominik; Bauer, Tanja; Bösmann, Andreas; Szesni, Normen; Libuda, Jörg; Wasserscheid, Peter
Abstract : Liquid organic hydrogen carriers represent an interesting alternative for hydrogen storage and transport. We demonstrate a method to simultaneously increase the activity of LOHC dehydrogenation catalysts and reduce side product formation. Abstract : Liquid organic hydrogen carrier (LOHC) systems are a promising alternative for energy storage and transport. The development of an active and selective LOHC-dehydrogenation catalyst is therefore of great importance. In this study we present a modification procedure of Pt/Al2 O3 catalysts with a sulfur containing compound that results in improved activity as well as in reduced side product formation. Here, it appears that the right amount of applied sulfur species is crucial to reach the described effects. The optimum value depends on the support surface area and the molar ratio of sulfur to surface platinum. Mechanistic studies of the sulfur modification by infrared spectroscopy (DRIFTS) with adsorbed CO revealed that preferentially low coordinated defect sites (edges or corner/apex Pt atoms) are blocked by sulfur compounds and that these are the ones responsible for side reactions. The sulfur species were found to modify the electronic properties of Pt and this facilitates the desorption of the aromatic dehydrogenation products.